Evaluation of Chemical Composition, Radical Scavenging and Antitumor Activities of Satureja hortensis L. Herb Extracts - Kristina Bimbiraitė-Survilienė; Mantas Stankevičius; Simona Šuštauskaitė; Agnieszka Gęgotek; Audrius Maruška; Elżbieta Skrzydlewska; Zita Barsteigienė; Ieva Akuņeca; Ona Ragažinskienė; Audronis Lukošius (MDPI AG, 2021)
Satureja hortensis L. is an annual herbaceous plant of the Lamiaceae Lindl. family. S. hortensis L., related to thyme and rosemary, is used as spice and traditional medicinal herb in Europe. Mainly due to the polyphenols contained in S. hortensis L., this plant exhibits multiple biological effects. However, therapeutic effects on cells, including skin tumors, have not yet been studied. Therefore, the aim of this study was to compare the composition and the resulting antioxidant as well as biological properties [on melanocytes and melanoma cells] of summer, savory growing in botanical garden of Vytautas Magnus University in middle Lithuania climatic conditions, collected during various phases of vegetation. It has been shown that the budding phase alcohol extract of this plant contains the largest amounts of polyphenols, including rutin and rosemary acid, which promote the radical scavenging activity and antioxidant properties. In contrast, the extract from the massive flowering phase already at a concentration of 12.5 µg/mL reduces the survival of melanoma cells to 60% with 90% melanocytes survival. In addition, extracts from beginning of flowering and end of flowering at a concentration of 25 µg/mL, containing significantly less rutin and rosmarinic acid, in combination with irradiation of cells with UVB, significantly increased the lipid peroxidation process, particularly in melanoma cells. These data indicate the possibility of using extracts from S. hortensis L. to modulate/differentiate the metabolism of normal and tumor skin cells.